2017
DOI: 10.3389/fmicb.2017.00564
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Compounds Produced by Vaginal Lactobacillus crispatus Are Able to Strongly Inhibit Candida albicans Growth, Hyphal Formation and Regulate Virulence-related Gene Expressions

Abstract: The female vaginal environment contains diverse microorganisms, and their interactions play significant roles in health and disease. Lactobacillus species are the predominant vaginal microorganisms in healthy women and relevant as a barrier to defense against pathogens, including Candida albicans. The yeast-to-hyphae transition is believed to be a determinant of C. albicans pathogenesis. In this study, we investigated the effects of vaginal isolates of L. crispatus (seven strains), L. gasseri (six strains), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 53 publications
2
112
2
Order By: Relevance
“…Initially it was suggested that antibiotic treatment removed lactobacilli from the vaginal mucosa, increasing vaginal pH, and promoting Candida hyphal formation. In agreement with this, lactobacilli have been proposed to reduce Candida colonisation [37], and have been explored as a potential probiotics [38]. However, other studies suggest that vaginal pH, and the lactobacilli population are not significantly altered in VVC [39], and that Candida colonisation is more common in women with a lactobacillus dominated microflora [40].…”
Section: Candida Albicans: the Ubiquitous Fungal Symbiontmentioning
confidence: 99%
“…Initially it was suggested that antibiotic treatment removed lactobacilli from the vaginal mucosa, increasing vaginal pH, and promoting Candida hyphal formation. In agreement with this, lactobacilli have been proposed to reduce Candida colonisation [37], and have been explored as a potential probiotics [38]. However, other studies suggest that vaginal pH, and the lactobacilli population are not significantly altered in VVC [39], and that Candida colonisation is more common in women with a lactobacillus dominated microflora [40].…”
Section: Candida Albicans: the Ubiquitous Fungal Symbiontmentioning
confidence: 99%
“…The metabolites of Lactobacillus spp. including organic acids, hydrogen peroxide, bacteriocins, and biosurfactants, all contribute to these antifungal effects [124,125]. However, only specific Lactobacillus strains are capable of producing these effectors in quantities required for antifungal activity, which possibly explains the failure of some vaginal lactobacilli to suppress Candida colonization.…”
Section: A Role For the Microbiome?mentioning
confidence: 99%
“…In support of this, down-regulation of hypha-specific transcriptional regulatory genes (EFG1, BCR1, and CPH1, etc.) and virulence related genes (HWP1, ALS3, ECE1, and SAP5) were observed during co-culture with lactobacilli or treatment with spent culture supernatant [125,127]. Lactobacilli were also reported to compete with the attachment of C. albicans to host cells, resulting in reduced adhesion to epithelial surfaces [128].…”
Section: A Role For the Microbiome?mentioning
confidence: 99%
“…Numerous studies have shown the considerable probiotic potential of L. crispatus, such as modulating the host's immune system [2], reducing allergic symptoms in mice [3], down-regulating the expression of cancer genes, and inhibiting the proliferation of MDA-MB-231 breast cancer cell lines [4]. In addition, as one of the most detected Lactobacillus species in the healthy female vagina [5], L. crispatus can inhibit vaginal pathogenic microorganisms, and maintain the health of the female reproductive system [6][7][8]. Moreover, clinical trials have shown the therapeutic effect of L. crispatus on female vaginitis and recurrent urinary tract infection [9,10].…”
Section: Introductionmentioning
confidence: 99%